Analisis Financial Distress dengan Menggunakan Metode Altman Z-Score pada PT. Cahaya Bintang Medan Tbk - Hafiza, Hafiza; Suprayitno, Eddi; Lubis, Farida Khairani (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This research aims to determine and analiyze the Altman Z-Score mothod in assessing the level of bankruptcy PT. Cahaya Medan Tbk for The 2018- 2021 period and to provide evidence that the altman Z-score method is effectively used in assessing the level of company bankruptcy with a relatively reliable level of precision and accuracy at PT.Cahaya Bintang Medan Tbk for the 2018-2021 period. The type of research used is quantitative descriptive analysis, namely by collecting, clarifying, analyzing and interpreting data obtained from the company so that it can provide a picture of the actual situatuin the calculation technique used in this reseatch is the Altman Z-Score model formula. Based on the results of calculations using the modified Altman Z-Score method from the 2018-2021 period, it shows that PT. Cahaya Bintang Medan Tbk is in the safe zone or safe because the average Z-Score value is above 2,60 or Z2,60